Epicardial adipose tissue volume but not density is an independent predictor for myocardial ischemia - Hell, Michaela M.; Ding, Xiaowei; Rubeaux, Mathieu; Slomka, Piotr; Gransar, Heidi; Terzopoulos, Demetri; Hayes, Sean; Achenbach, Stephan; Berman, Daniel S.; Dey, Damini; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
BACKGROUND: Epicardial adipose tissue (EAT) volume is associated with plaque formation and cardiovascular event risk, its density may reflect tissue composition and metabolic activity. OBJECTIVES: Global and regional associations between EAT volume and density, ischemia and coronary calcium were investigated using a novel automatic quantitative measurement software. METHODS: 71 patients with an intermediate pre-test probability for coronary artery disease and inducible ischemia by SPECT were matched to two same-gender controls (total of 213 patients, 90% male, age 60 ± 10 years). Non-contrast CT for assessment of EAT volume, density (in Hounsfield Unit [HU]) and coronary calcium score (CCS) was performed. RESULTS: Global EAT volume was significantly increased in ischemic patients compared to controls (96 ± 49 vs. 82 ± 36 cm(3), p = 0.04), density showed no significant difference (-75.6 ± 4.3 vs. -75.1 ± 4.1HU, p = 0.63). EAT volume and density differed significantly between coronary territories (LAD: 37 ± 18 cm(3), -77.8 ± 4.5HU; LCx: 16 ± 9 cm(3), -73.9 ± 4.1HU; RCA: 36 ± 17 cm(3), -71.7 ± 4.8HU, p < 0.001). For regional ischemia, only LCx territory showed a significantly higher EAT volume (18 ± 8 vs. 16 ± 9 cm(3), p = 0.048). Multivariable logistic regression revealed a significant association with ischemia for EAT volume (OR 2.09 (1.0; 4.3), p = 0.049) and CCS (OR 1.43 (1.1; 1.9), p = 0.006). EAT volume significantly improved discrimination of ischemia over CCS (Integrated Discrimination Improvement: 3.5%, 95%CI: 1.1-6.1%, p = 0.004). Hypertension was the only risk factor significantly influencing EAT volume and density (98 ± 48 vs. 78 ± 31 cm(3), p = 0.002, -76.0 ± 4.1 vs. -74.5 ± 4.1 HU, p = 0.01). CONCLUSIONS: EAT volume is associated with myocardial ischemia and improves the discriminative power for independent ischemia prediction over CCS. In hypertensive patients, EAT is characterized by lower density and higher volumes.
EVALuna2:12102